Hostage ebook A novel. - Mackintosh, Clare (2021)
"Feels like a blockbuster movie."—Lisa Jewell, #1 New York Times bestselling author of Then She Was Gone "Mackintosh is a pro...the final scene in the book almost made me sick as I read it. I mean that as a compliment of the highest order."—The New York Times You can save hundreds of lives. Or the one that matters most... From New York Times bestselling author Clare Mackintosh comes a claustrophobic thriller set over 20 hours on-board the inaugural nonstop flight from London to Sydney. Mina is trying to focus on her job as a flight attendant, not the problems with her five-year-old daughter back home, or the fissures in her marriage. But the plane has barely taken off when Mina receives a chilling note from an anonymous passenger, someone intent on ensuring the plane never reaches its destination: "The following instructions will save your daughter's life..." Someone needs Mina's assistance and knows exactly how to make her comply. When one passenger is killed and then another, Mina knows she must act. But which lives does she save: Her passengers...or her own daughter and husband who are in grave distress back at home? It's twenty hours to landing. A lot can happen in twenty hours. For fans of the locked-room mystery of One by One and the heart-stopping tension The Last Flight, Hostage is an explosively addictive thriller about one flight attendant and the agonizing decision that will change her life—and the lives of everyone on-board—forever. Praise for Hostage: "A banger of a book with a truly agonizing 'what would you do?'" — Ruth Ware, #1 New York Times bestselling author of One by One "Hypnotically good. Should be a hit, could be a classic..." — Lee Child, #1 New York Times bestselling author of the Jack Reacher series "Fiendishly clever." — Lisa Gardner, #1 New York Times bestselling author of Before She Disappeared "A propulsive read." — Karin Slaughter, New York Times bestselling author of The Silent Wife "A nail-biter of a thriller." — Shari Lapena, New York Times bestselling author of The Couple Next Door